Symposium on the Idea of a University in the 1990s - Gibson, Norman (Statistical and Social Inquiry Society of Ireland, 1990)
In the centenary year of Cardinal Newman's death and when universities and higher education are under widespread and critical appraisal it is fitting and timely that the Statistical and Social Inquiry Society of Ireland with its long and distinguished history should hold a symposium on this subject. It is a great privilege to take part in it.
The idea of a university in the 1990s
Read before the Society, 29 March, 1990
Keywords: Third level education; Educational finance; 314.15